Wnt pathway modulators in cancer therapeutics: An update on completed and ongoing clinical trials. Issue 5 (11th October 2021) - Neiheisel, Ann; Kaur, Manpreet; Ma, Nancy; Havard, Patty; Shenoy, Anitha K.
Abstract: Wnt signaling plays an essential role in the initiation and progression of various types of cancer. Besides, the Wnt pathway components have been established as reliable biomarkers and potential targets for cancer therapy. Wnt signaling is categorized into canonical and noncanonical pathways. The canonical pathway is involved in cell survival, proliferation, differentiation and migration, while the noncanonical pathway regulates cell polarity and migration. Apart from its biological role in development and homeostasis, the Wnt pathway has been implicated in several pathological disorders, including cancer. As a result, inhibiting this pathway has been a focus of cancer research with multiple targetable candidates in development. In this review, our focus will be to summarize information about ongoing and completed clinical trials targeting various Wnt pathway components, along with describing current and emerging Wnt targeted therapies. In addition, we will discuss potential opportunities and associated challenges of inhibiting Wnt signaling for cancer therapy.